Implementation of a hydrogen fuel cell in a small urban vehicle - Michal Cenkner; Premysl Toman; Josef Svoboda (Acta Polytechnica CTU Proceedings)
The transition to sustainable urban mobility is a key priority for Europe as countries seek to reduce greenhouse gas emissions and combat climate change. Electric vehicles (EVs) have become a popular trend offering a cleaner alternative to traditional combustion engines. However, despite their advantages, EVs face challenges related to the difficult extraction of raw materials for battery production, energy storage and long charging times. Hydrogen fuel cells (HFCs) are another possible alternative, offering longer range and shorter refueling times while maintaining zero local emissions. This paper discusses the integration of hydrogen fuel cell technology into a small urban vehicle and evaluates its potential in terms of sufficient power and efficiency. The study focuses on the design and implementation of the fuel cell system in a specific prototype vehicle, with the biggest challenge being the placement of the components and definition of sufficient power of fuel cell system integrated as range extender.